O problema da moral cristã na genealogia da moral de Nietzsche - Vasconcelos, Rafaela Mendonça de Almeida (2023)
The present work aims to study the genealogical criticism that Nietzsche makes in relation to the influence that Christian morality exerts on the man who follows it, as well as highlighting the idea of values, good and bad and good and bad, it is revealed that in this way This is how the transmutation of moral values takes place. With this, we highlight the way in which it, Christian morality, conditions you to oppress your wills and desires, triggering a bad conscience and, in turn, leading you to resentment. This dissertation observes and analyzes how Nietzsche's texts helped us to carry out our study, having as its main work Nietzsche's Genealogy of Morals (2009), as well as other works by the philosopher: Beyond Good and Evil (2005), The Will of Power (2011), the Antichrist (2020), Thus Spoke Zaratustra (2018), among other commentators and works around the theme that we are willing to study. In this aspect, our work elucidates the issue of the value of moral values within the scope of the Judeo-Christian revolution in Western culture, the idea of good and bad/evil, as well as the concepts of bad conscience, guilt (Schuld) and ascetic ideals, all related to the morality of resentment. Finally, we come to the conclusion that the transmutation of moral values ends up benefiting the domain of Judeo-Christian morality, intervening in the vision we have of ourselves and others, conceiving someone as good or bad and that with this, man tries to become surpass others to become superior.